Clinical outcomes of adjuvant external-beam radiotherapy for differentiated thyroid cancer - Biermann, M.; Pixberg, M. K.; Riemann, B.; Schuck, A.; Heinecke, A.; Schmid, K. W.; Willich, N.; Dralle, H.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2009)
Aim: Evaluate the clinical benefit of external beam radiotherapy (RTx) for locally invasive thyroid carcinoma with follicular cell differentiation (DTC). Patients, methods: The Multicentre Study on Differentiated Thyroid Cancer (MSDS) was planned as a prospective multicenter trial on the benefit of adjuvant RTx in locally invasive DTC (pT4; UICC 1997) with or without lymph node metastases and no known distant metastases. All patients were treated with thyroidectomy, 131I-therapy, and TSH-suppression and were randomized to receive additional RTx or not. In 4/2003 the trial became a prospective cohort study after only 45 of then 311 patients had consented to randomization. 351 of 422 patients met the trial's inclusion criteria. Age was 48 ± 12 years (mean ± SD). 25% were men. Tumours were papillary in 90% and follicular in 10%. Of 47 patients randomized or allocated to RTx, 26 actually received RTx. Results: Mean followup was 930 days. In an actual treatment analysis, 96% (25/26) of the RTx-patients reached complete remission (CR) vs. 86% in the non-RTx patients. Recurrences occurred in 0 vs. 3 % of patients: 6 reoperated for regional lymph node metastases, 1 tracheal invasion treated with tracheoplasty, 1 local invasion necessitating laryngectomy, 2 distant metastases (1 lung, 1 lung + bone). Serious chronic RTx toxicity occurred in 1/26 patients. Conclusion: The MSDS trial showed low mortality and recurrence rates and a weak benefit of RTx in terms of local control that did however not reach statistical significance. Routine RTx in locally invasive DTC can no longer be recommended .
Keywords: Thyroid cancer; external beam radiotherapy; radioiodine treatment; survival